Voluntary Ingestion of a Cola Nut Stuck into the Esophagus: An Unusual Foreign Body (FB) - Lawani, ismail; GBESSI, GASPARD DANSOU; KPOSSOU, ABOUDOU RAÏMY; YACOUBOU, IMOROU SOUAIBOU; GNANGNON, FREDDY HOUEHANOU RODRIGUE; DOSSOU, FRANCIS MOÏSE DJIDÉNOU; MEHINTO, KUASSI DELPHIN; OLORY-TOGBE, JEAN-LÉON TOUSSAINT (My University, 2016)
The cola nut (Cola nitida), is a rare foreign body. Its voluntary ingestion, for ritual practices, is a situation of exceptional occurrence, and jamming it in the esophagus is a therapeutic emergency. Here, we report the case of an adult patient, with a cola nut measuring 3 cm in diameter swallowed for a ritual purpose, jammed at the bottom of his esophagus. A surgical extraction was performed by gastrostomy after a failed attempt of endoscopic extraction. There ensued a complication of a left-esophageal fistula. The various aspects of this case are analyzed in the light of the literature review.
Keywords: Foreign Body; Esophagus; Cola Nut; Gastrostomy